Local C-Reactive Protein Expression in Obliterative Lesions and the Bronchial Wall in Posttransplant Obliterative Bronchiolitis - Outi E. Päiväniemi; Paula K. Maasilta; Tiina L. S. Vainikka; Hanni S. Alho; Pekka J. Karhunen; Ulla-Stina Salminen (Mediators of Inflammation)
The local immunoreactivity of C-reactive protein (CRP) was studied in a heterotopic porcine model of posttranplant obliterative bronchiolitis (OB). Bronchial allografts and control autografts were examined serially 2–28 days after subcutaneous transplantation. The autografts stayed patent. In the allografts, proliferation of inflammatory cells (P<.0001) and fibroblasts (P=.02) resulted in occlusion of the bronchial lumens (P<.01). Influx of CD4+ (P<.001) and CD8+ (P<.0001) cells demonstrated allograft immune response. CRP positivity simultaneously increased in the bronchial walls (P<.01), in macrophages, myofibroblasts, and endothelial cells. Local CRP was predictive of features characteristic of OB (R=0.456–0.879, P< .05−P<.0001). Early obliterative lesions also showed CRP positivity, but not mature, collagen-rich obliterative plugs (P<.05). During OB development, CRP is localized in inflammatory cells, myofibroblasts and endothelial cells probably as a part of the local inflammatory response.